Sir Robert Peel : statesmanship, power and party - Evans, Eric J., 1945- (London ; New York : Routledge, 2006)
Eric Evans presents an introduction to the life and career of British Prime Minister, Sir Robert Peel. The author reassesses Peel's career, arguing that although his executive and administrative strengths were great, he presented political problems which he was incapable of solving.
Chapter 1 Introduction -- chapter 2 The young statesman, 1809-18 -- chapter 3 Peel, the Home Oﬃce and 'Liberal Toryism', 1819-30 -- chapter 4 The collapse of the old Tory party, 1827-32 -- chapter 5 A King's minister out of oﬃce: Peel in the 1830s -- chapter 6 Revival: Toryism into Conservatism, 1832-41 -- chapter 7 The general election of 1841 -- chapter 8 Executive government under Peel, 1841-6 -- chapter 9 Peel and backbench Toryism, 1841-5 -- chapter 10 The repeal of the Corn Laws and the fall of Peel -- chapter 11 Conclusion: Reputation and evaluation, 1846-50 and beyond.
Includes bibliographical references (pages 89-95) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Peel, Robert, -- 1788-1850.; Conservative Party (Great Britain) -- History -- 19th century; Peel, Robert, -- 1788-1850; Conservative Party (Great Britain); Prime ministers -- Great Britain -- Biography; Great Britain -- Politics and government -- 1837-1901.; Great Britain -- Politics and government -- 1830-1837.; Grande-Bretagne -- Politique et gouvernement -- 1837-1901.; Grande-Bretagne -- Politique et gouvernement -- 1830-1837.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Politics and government; Prime ministers; Great Britain; 1800-1901; Electronic books; Biographies; History